1999
DOI: 10.1046/j.1365-2168.1999.01202.x
|View full text |Cite
|
Sign up to set email alerts
|

Intragraft expression of transforming growth factor β1 gene in isolated glomeruli from human renal transplants

Abstract: TGF-beta1 is a profibrotic influence in human renal transplants. The methods described should prove of benefit in investigating the mechanisms of chronic renal allograft damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Immunohistochemistry has shown that kidneys with CNI-induced morphologic abnormalities express the cytokine TGF-␤1 (21)(22)(23)(24). Furthermore, stimulation of the TGF-␤1 production in vivo after the use of CNI has been described by several groups.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Immunohistochemistry has shown that kidneys with CNI-induced morphologic abnormalities express the cytokine TGF-␤1 (21)(22)(23)(24). Furthermore, stimulation of the TGF-␤1 production in vivo after the use of CNI has been described by several groups.…”
Section: Discussionmentioning
confidence: 97%
“…For codon 10, 82.5% in the ESRFϩ group versus 56.1% in the ESRF-group were Pro-carriers (Pϭ0.0003). For codon 25,24.6% in the ESRFϩ group versus 10% in the ESRF-group were Pro-carriers (Pϭ0.008). None of the patients who were homozygote for leucine at codon 10 were pro-carriers at codon 25.…”
Section: Tgf-␤1 Gene Polymorphismsmentioning
confidence: 95%
“…When TGF-b was directly injected into the subcutaneous tissue of newborn mice, accelerated fibrosis, that is, activation of fibroblasts to produce collagens, was demonstrated (Roberts et al, 1986;Shinozaki et al, 1997). In clinical diseases including pulmonary fibrosis and chronic renal allograft damage, TGF-b is also considered to be a main pathogenic factor for the overproduction of collagen (Nicholson et al, 1999). Obviously, TGF-b is not the only factor that can stimulate collagen expression in fibroblasts, since insulin and/or growth factors analysed here also regulate the production of type I collagen (Krupsky et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Increased renal allograft expression of TGF-b also occurs in the clinical setting 98,99 . Nicholson et al 100 examined intragraft gene expression in glomeruli using a RT PCR and found a positive correlation between the level of glomerular complementary DNA for TGF-b and renal cortical collagen III immunostaining (P < 0´01). Intragraft TGF-b levels also correlate with a decline in allograft function.…”
Section: Angiotensin II Increases Ecm Deposition Via Tgf-b Induces Upmentioning
confidence: 99%